Ação antimicrobiana e antioxidante in vitro das frações proteicas da microalga Scenedesmus obliquus - Lima, Rejane Maria Moreira (2016)
The increase in research involving the extraction of biologically active compounds microalgae has recently around the world, thanks to the advancement of studies that demonstrate its potential biotechnology, and medical nutrition. The aim of this study was to evaluate the productivity of chlorophyll a, the rate of cell growth and the soluble protein content of microalgae obliquus Scenedesmus grown in vertical photobioreactor amid toilet cultivation (Water Culture) modified under controlled conditions of temperature and light. In addition, we evaluated the protein fractions subjected to precipitation with ammonium sulfate at different levels of saturation (0-20%, 20-40%, 40-60% and 60-80%), as the antifungal activity, using the disk diffusion method, and the antioxidant activity using the DPPH (1,1-diphenyl-2-picrylhydrazyl). There was the quantification of the essential amino acid content present in the fraction with the highest activity. The results showed a production of 8.5 mg chlorophyll a / L Cell density Maximum (DCM) was 130 x 105 cells / ml and the protein concentration measured in protein fractions ranged from 0.485 to 1.042 mg / ml. The electrophoretic pattern of protein fractions delineated by a wide range of molecular weight ranging from 116 kDa and 14.4 kDa, predominantly greater concentration of proteins in the range between 21.5 and 45 kDa. The protein fractions tested (FrP0-20% FrP20-40% FrP40-60% and FrP60-80%) had antimicrobial effect against C. kefyr fungus, A. niger and A. fumigatus, but only a fraction FrP40-60 % and the control treatment showed inhibition zone for C. albicans. No treatment had inhibitory effect of growth of bacteria S. epidermidis, E. coli and P. aeruginosa. Only FrP fractions 40-60% and FrP60-80% showed growth inhibition of S. aureus. The FrP40-60% fraction showed superior results in all analyzes with a maximum of 85% antioxidant effect at a concentration of 0.8 mg / mL. Quantitative analysis of essential amino acids revealed the presence of Cys, Lys, Leu, Phe, Thr, Tyr, Val, Met, Ile and Trp. The results showed that Scenedesmus obliquus is a promising source of biocompounds that can be used in the manufacture of food supplements for humans and animals, cosmetics and medicines preparation.